Al-sa‘adah dalam Al-Quran dan Al-Sunnah: analisis pandangan Shah Wali Allah Al-Dihlawi / Noraini Junoh - Junoh, Noraini (2018)
Every person has his or her own definition and view on a meaning of happiness and most of us relate it with materialistic. This study was conducted to help us to understand a concept of al-sa‘adah or a true definition of happiness in greater details. It highlights on the happiness based on a manuscript entitled Hujjah Allah al-Balighah written by Shah Wali Allah which is based on al-Quran and al-Sunnah views and also a main reference of this study. Besides that, this study used any primary and secondary sources available at a library and the study was written as a qualitative. A conceptual framework used in this study was improvised based on content method analysis. Based on the findings, it shows that the concept of al-sa‘adah proposed by Shah Wali Allah corresponds to the views in al-Quran and al-Sunnah. He stresses that the most awaiting and exciting happiness of a person is the hereafter.